Study on Quality Clay Kenagarian Sibusuk Padang Kecamatan Kupitan Kabupaten Sijunjung - Fitri, Octavialdi Pandora (STKIP PGRI Sumbar, 2014)
This study aims to find out about Clay Quality Study in Kenagarian Padang Kecamatan Sibusuk KupitanKabupaten Sijunjung .The method used in this research is descriptive method, by means of sampling in this study is purposivesampling method (Sample Select). There are 3 samples. Samples 1 Kapalo koto western region, the central part ofSample2, Sample 3 Kapalo koto eastern regionThe results showed that: 1). The physical properties of the soil, a), soil texture based analysis of soil texturewas obtained from the laboratory test results, the obtained two dusty clay loam texture that is present in sample 1and sample 2, then clay dust found in samples 3 b), based on observations of soil structure there are two structuresthat the sample 1 and sample 2, has a blocky soil structure with a very good category, while the structure of the soilsample 3 has a fine granular structure. c). Consistency ground based observations in the field are presented, thenthere are two categories of soil consistency measurements conducted field measurements that the samples 1 and 2were categorized either sample, whereas in the ugly category 3 samples. 2). The nature of the soil pH based on soilpH measurement results obtained from laboratory analysis, there are two categories of soil pH measurements onsample 1 and sample 3 has an acidic pH with both categories and sample 2 has an acidic pH medium category. 3).Biological properties of soil (organic matter) based on the results of measurements of soil organic matter derivedfrom laboratory analysis, which is a very good category.